2018
DOI: 10.1021/acs.jafc.8b00790
|View full text |Cite
|
Sign up to set email alerts
|

pH-Signaling Transcription Factor AopacC Regulates Ochratoxin A Biosynthesis in Aspergillus ochraceus

Abstract: In Aspergillus and Penicillium species, an essential pH-response transcription factor pacC is involved in growth, pathogenicity, and toxigenicity. To investigate the connection between ochratoxin A (OTA) biosynthesis and ambient pH, the AopacC in Aspergillus ochraceus was functionally characterized using a loss-of-function mutant. The mycelium growth was inhibited under pH 4.5 and 10.0, while the sporulation increased under alkaline condition. A reduction of mycelium growth and an elevation of sporulation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 46 publications
(117 reference statements)
1
35
0
1
Order By: Relevance
“…It has been already reported that OTA biosynthesis is regulated by PacC in Aspergillus ochraceus (Wang et al, 2018). Although the growth of the AopacC mutant and its ability to produce OTA were compromised to some degree, an increase in conidia formation has been observed compared to that of the wild type strain, suggesting that PacC in A. ochraceus positively regulates growth and OTA biosynthesis, but has a negative regulatory role in sporulation.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…It has been already reported that OTA biosynthesis is regulated by PacC in Aspergillus ochraceus (Wang et al, 2018). Although the growth of the AopacC mutant and its ability to produce OTA were compromised to some degree, an increase in conidia formation has been observed compared to that of the wild type strain, suggesting that PacC in A. ochraceus positively regulates growth and OTA biosynthesis, but has a negative regulatory role in sporulation.…”
Section: Introductionmentioning
confidence: 89%
“…AcpacC strain, an increase in conidia formation was observed in A. ochraceus pacC mutant compared to that of the WT strain under all the pH conditions (Wang et al, 2018). Therefore, it is likely that PacC plays different roles in mycelial growth and sporulation of different fungal pathogens.…”
Section: Acpacc Is Required For Fungal Growth Conidial Formation Andmentioning
confidence: 95%
See 2 more Smart Citations
“…De fato, quanto à A. nidulans, são as enzimas xilanolíticas e celulolíticas as menos expressas na presença de glicose(RIES et al, 2016), podendo haver especificidades e funcionalidades distintas entre as duas espécies. no perfil de expressão de genes relacionados com enzimas amilolíticas no gênero Aspergillus(YIN et al, 2017;WANG et al, 2018), podendo haver uma relação com os resultados observados. O tampão fosfato pôde não apenas atuar na regulação de pH, mas também fornecer íons e cofatores para enzimas importantes de seu metabolismo celular, o que justificaria o aumento na produção de proteínas extracelulares, Bbl1 e crescimento em biomassa.Ambas agitação e aeração são importantes em todos os processos aeróbicos; aumento no balanço ATP/ADP, NAD + /NADH, glicólise, fosforilação oxidativa, metabolismo de proteínas e, pela homogeneização do meio, garantindo acesso igual aos nutrientes e oxigênio dissolvidos no meio(ZHOU et al, 2018).…”
unclassified